Nano composite material with heterogeneous hollow multi-shell structure as well as preparation method and application of nano composite material

By using a heterogeneous hollow multi-shell structure MoS2/FeS@NC nanocomposite material in the negative electrode material of sodium ion battery, using built-in electric field and nitrogen-doped carbon coating, the shortcomings in the existing materials in Na+ transmission kinetics and cyclic stability are solved, and more efficient electrochemical performance and sodium storage ability are achieved.

CN119650668AActive Publication Date: 2025-03-18QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510092192.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-03-18
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode materials are single in structural design, with slow Na+ transmission dynamics and poor cycle stability, making it difficult to meet the practical application needs.

Method used

The nanocomposite material with a heterogeneous hollow multi-shell structure is formed by composite of MoS2 and FeS, and is coated with nitrogen-doped carbon in the outermost layer. It constructs a built-in electric field with the heterogeneous interface between metal sulfide through a unique morphological design to improve the electrochemical performance of the material.

Benefits of technology

It significantly improves Na+ transmission kinetics and cyclic stability, provides a large specific surface area and high porosity, alleviates the volume expansion problem during sodium storage, and improves conductivity and sodium storage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650668A_ABST
    Figure CN119650668A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of new energy materials, and particularly relates to a nano composite material with a heterostructure and a hollow multi-shell morphology and a preparation method and application of the nano composite material. The nano composite material is formed by coating the surface of bimetallic sulfide with nitrogen-doped carbon, and the bimetallic sulfide is formed by compounding MoS2 and FeS; the nano composite material is of a porous hollow multi-shell nanosphere structure, and gaps are reserved between inner shells of the hollow multi-shell structure. The material is used as a negative electrode material of a Na < + > battery and has excellent electrochemical performance. Benefited from the advantages of a built-in electric field formed by a heterostructure and a unique hollow multi-shell morphology structure, the composite material shows remarkable cycling stability and rate capability, and has rapid Na < + > transmission dynamics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new energy materials and relates to a nanocomposite material with a heterogeneous hollow multi-shell structure and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Transition metal sulfides have attracted extensive attention as electrode materials for sodium ion batteries due to their high theoretical capacity, simple preparation process, and excellent electrochemical reversibility. However, traditional single transition metal sulfides usually exhibit poor conductivity, insufficient cycle stability, and Na + Defects such as slow transport kinetics have greatly limited its development in practical applications. To overcome the above shortcomings, researchers have significantly improved its electrochemical performance by optimizing the morphology design of the material and constructing a composite multimetallic sulfide heterostructure. However, the inventors further found that the application of existing negative electrode materials in sodium-ion batteries still faces many challenges, such as single structural design, Na + Problems such as slow transfer dynamics and poor cyclic stability urgently need further improvement. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art, the present invention provides a heterogeneous hollow multi-shell structure nanocomposite material and its preparation method and application. Through the unique morphology design and the built-in electric field constructed by the metal sulfide heterogeneous interface, the composite material exhibits excellent cycle stability, high efficiency Na + Transport kinetics, large specific surface area and good electrolyte wettability provide a new solution for the performance optimization of sodium-ion battery negative electrode materials.

[0005] In order to achieve the above object, the technical solution of the present invention is:

[0006] In the first aspect, a heterogeneous hollow multi-shell nanocomposite material is provided, wherein the nanocomposite material is formed by nitrogen-doped carbon coated on the surface of a bimetallic sulfide, wherein the bimetallic sulfide is formed by a composite of MoS2 and FeS; the nanocomposite material is a porous hollow multi-shell nanosphere structure, wherein gaps are left between the shells inside the hollow multi-shell structure.

[0007] The heterogeneous hollow multi-shell nanocomposite material provided by the present invention is formed by combining MoS2 and FeS, and the outermost layer is coated with nitrogen-doped carbon. Its unique heterogeneous structure significantly improves the performance of the material. The nanocomposite material presents a porous hollow three-shell nanosphere structure, and appropriate gaps are retained between each shell layer, which is Na + The transport provides an efficient channel while enhancing the structural stability and electrochemical performance of the material.

[0008] Compared with traditional single transition metal sulfide electrode materials, the MoS2 / FeS@NC composite material proposed in this invention is constructed by two transition metal sulfides, iron and molybdenum. Through the built-in electric field formed at the interface between iron sulfide and molybdenum sulfide crystals, this material significantly accelerates the Na + The transport kinetics further promote the efficient electrochemical reaction.

[0009] In addition, the hollow three-shell structure formed by the present invention has a large specific surface area, and its rich heterogeneous structure interface can provide a large number of reactive sites. The gaps between the shells in the multi-shell structure effectively alleviate the volume expansion problem of the electrode material during the sodium storage process. At the same time, through the composite with carbon materials, not only can the agglomeration problem of the negative electrode material be significantly alleviated, but also its conductivity can be improved. In addition, doping nitrogen atoms in carbon materials can effectively regulate the electronic structure of the composite material, promote charge transfer and increase specific capacity. Therefore, the nanocomposite material provided by the present invention significantly improves the Na + The transport dynamics of electrons and ions in the battery show excellent cycle stability and rate performance, as well as rapid sodium storage performance.

[0010] On the other hand, a method for preparing the above-mentioned heterogeneous hollow multi-shell structured nanocomposite material comprises the following steps:

[0011] Sucrose is dissolved in water and subjected to hydrothermal reaction to obtain carbonaceous nanospheres;

[0012] The carbon nanospheres were placed in a solution containing citric acid, trivalent iron (Fe 3+ ) and molybdate (MoO4 2- ) solution, and then aging the aged carbonaceous nanospheres in an air atmosphere to obtain a hollow three-shell Fe2(MoO4)3 precursor;

[0013] The Fe2(MoO4)3 precursor and sulfur powder are subjected to a vapor phase sulfurization treatment in an inert atmosphere to obtain a hollow three-shell MoS2 / FeS. The vapor phase sulfurization process used in the present invention can retain the internal morphology of the hollow three-shell of the Fe2(MoO4)3 precursor to the greatest extent, ensuring that the obtained product has a complete hollow three-shell structure;

[0014] MoS2 / FeS is mixed with dopamine, and dopamine polymerization is performed to obtain a polydopamine-coated MoS2 / FeS precursor;

[0015] Under inert atmosphere conditions, the polydopamine-coated MoS2 / FeS precursor is subjected to a second calcination to obtain the product.

[0016] The preparation method of the present invention can prepare the above-mentioned heterogeneous structure hollow multi-shell structure nanocomposite material, and the prepared material has high structural stability, uniformity and dispersibility, so that it has excellent sodium storage performance.

[0017] In a third aspect, a nanocomposite material having a heterogeneous hollow multi-shell structure is used for preparing a sodium ion battery.

[0018] In a fourth aspect, a negative electrode for a sodium ion battery comprises an active material, a conductive agent, a binder and a current collector, wherein the active material is the above-mentioned heterogeneous hollow multi-shell structured nanocomposite material.

[0019] In a fifth aspect, a sodium ion battery comprises a positive electrode, a negative electrode and a secondary electrolyte, wherein the negative electrode is the negative electrode of the sodium ion battery described above.

[0020] The beneficial effects of the present invention are:

[0021] 1. The heterogeneous hollow multi-shell nanocomposite material provided by the present invention is composed of two transition metal sulfides, iron and molybdenum. The material forms a built-in electric field through the heterogeneous structure between the two crystal interfaces, which can significantly improve the Na + transport kinetics and effectively reduce the internal resistance of the material, thereby further optimizing its electrochemical performance.

[0022] 2. The present invention adopts hydrothermal reaction, aging and calcination methods to prepare heterogeneous transition metal sulfide / nitrogen-doped carbon nanocomposites with hollow multi-shell structures. The synthesis process is simple, easy to operate, green and environmentally friendly, and has low energy consumption.

[0023] 3. The heterogeneous hollow multi-shell nanocomposite prepared by the present invention has a unique three-layer shell structure, showing excellent properties such as large specific surface area and high porosity. This structure can effectively alleviate the volume expansion during sodium storage, significantly shorten the diffusion path of ions, and improve the efficiency of ion transmission and transport, thereby accelerating the electrochemical reaction.

[0024] 4. The heterogeneous hollow multi-shell structure nanocomposite material provided by the present invention alleviates the aggregation problem of negative electrode materials and improves its own conductivity by compounding with carbon materials.

[0025] 5. The heterogeneous hollow multi-shell structure nanocomposite material provided by the present invention is coated with nitrogen-doped carbon. Due to the doping of nitrogen atoms, it is beneficial to charge transfer and provides a larger capacity.

[0026] 6. The sodium ion battery prepared with the heterogeneous hollow multi-shell structure nanocomposite material provided by the present invention as the negative electrode material shows excellent cycle stability and rate performance in electrochemical tests. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0028] Figure 1 Electron microscope images of the Fe2(MoO4)3 precursor prepared in Example 1 of the present invention, (a) is a scanning electron microscope image (SEM); (b) is a transmission electron microscope image (TEM);

[0029] Figure 2 Electron microscope images of the MoS2 / FeS@NC composite material with a hollow multi-shell structure prepared in Example 2 of the present invention, (a) is a scanning electron microscope image (SEM); (b) is a transmission electron microscope image (TEM);

[0030] Figure 3 XRD diagram of the MoS2 / FeS@NC composite material with a hollow multi-shell structure prepared in Example 2 of the present invention, where the ordinate is the relative diffraction intensity and the abscissa is the 2θ diffraction angle;

[0031] Figure 4 This is the XPS overall spectrum of the MoS2 / FeS@NC composite material with a hollow multi-shell structure prepared in Example 3 of the present invention;

[0032] Figure 5 The MoS2 / FeS@NC composite material with a hollow multi-shell structure prepared in Example 4 of the present invention was subjected to a current density of 2A·g –1 The cycle performance curve diagram below;

[0033] Figure 6 The MoS2 / FeS@NC composite material with a hollow multi-shell structure prepared in Example 5 of the present invention is subjected to a current density of 0.1 to 10 A·g –1 Battery charge and discharge curve diagram of the lower rate performance test. DETAILED DESCRIPTION

[0034] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0035] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0036] As described in the background technology, the prior art has the following problems: + In order to solve the above technical problems, the present invention proposes a nanocomposite material with a heterogeneous hollow multi-shell structure and a preparation method and application thereof.

[0037] A typical embodiment of the present invention provides a nanocomposite material with a heterogeneous hollow multi-shell structure, wherein the nanocomposite material is formed by nitrogen-doped carbon coated on the surface of a bimetallic sulfide, and the bimetallic sulfide is formed by a composite of MoS2 and FeS; the nanocomposite material is a porous hollow multi-shell nanosphere structure, and gaps are left between the shells inside the hollow multi-shell structure.

[0038] The heterogeneous hollow multi-shell structure nanocomposite material provided by the present invention has significant characteristics such as large specific surface area and high porosity, providing sufficient channels and free space for ion transmission, thereby effectively adapting to the volume expansion during sodium storage. In addition, through the combination with carbon materials and the doping of nitrogen atoms, the material significantly alleviates the aggregation problem of negative electrode materials, while greatly improving the conductivity and sodium storage performance.

[0039] In some examples of this embodiment, the diameter of the nanosphere structure is 800-2000 nm.

[0040] Another embodiment of the present invention provides a method for preparing the above-mentioned heterogeneous hollow multi-shell structure nanocomposite material, comprising the following steps:

[0041] Sucrose is dissolved in water and subjected to hydrothermal reaction to obtain carbonaceous nanospheres;

[0042] The carbon nanospheres are placed in a solution containing citric acid, trivalent iron salt and molybdate for aging. The rich oxygen-containing groups on the surface of the carbon nanospheres will capture the iron ions (Fe 3+ ) and molybdate (MoO4 2- );

[0043] The aged carbonaceous nanospheres were first calcined in an air atmosphere to obtain a hollow three-shell Fe2(MoO4)3 precursor;

[0044] The Fe2(MoO4)3 precursor and sulfur powder are subjected to a vapor phase sulfurization treatment in an inert atmosphere to obtain a hollow three-shell MoS2 / FeS;

[0045] MoS2 / FeS is mixed with dopamine, and dopamine polymerization is performed to obtain a polydopamine-coated MoS2 / FeS precursor;

[0046] Under inert atmosphere conditions, the polydopamine-coated MoS2 / FeS precursor is subjected to a second calcination to obtain the product.

[0047] The heterogeneous hollow multi-shell nanocomposite material synthesized by the hard template method has the characteristics of uniform size and good crystallinity. The crystal interface of the heterogeneous structure in the material forms a built-in electric field, which significantly improves the activity of metal sulfides and shows excellent Na + In addition, the unique hollow multi-shell structure of this material has a large specific surface area and high porosity, which can effectively adapt to Na + The volume expansion during the insertion / extraction process alleviates the aggregation problem of the negative electrode material and significantly improves its conductivity and sodium storage performance.

[0048] The ferric salt described in the present invention refers to a compound containing ferric ions, such as ferric chloride, ferric nitrate and ferric acetate.

[0049] The molybdate described in the present invention refers to a compound containing molybdate ions, such as ammonium molybdate, sodium molybdate, and the like.

[0050] The hydrothermal reaction described in the present invention refers to a reaction in which the reactants are dissolved in water in a certain proportion in a closed system and then placed in an autoclave at a certain temperature and autogenous pressure of the solution, and the original mixture undergoes a reaction.

[0051] In some examples of this embodiment, the molar ratio of the ferric salt to the molybdate is 1:0.45-0.55.

[0052] In some examples of this embodiment, the temperature of the hydrothermal reaction is 160-190° C., and the time is 1-1.5 h.

[0053] In some examples of this embodiment, the solvent used in the aging solution is a mixture of water and ethanol. Specifically, the volume ratio of ethanol to water is 1:2.5-3.5.

[0054] In some examples of this embodiment, the aging temperature is 40 to 70° C. The aging efficiency is higher under this condition. Specifically, the aging time is 12 to 60 hours.

[0055] In some examples of this embodiment, the temperature of the first calcination is 450-550° C. Specifically, the first calcination time is 2-3 hours.

[0056] In some examples of this embodiment, the temperature of the gas phase vulcanization treatment is 350-450° C. Specifically, the time of the gas phase vulcanization treatment is 3-5 hours.

[0057] In some examples of this embodiment, the addition ratio of MoS2 / FeS precursor and sulfur powder is 1:0.9-1.1.

[0058] In some examples of this embodiment, the pH value of the dopamine polymerization reaction is 8.0-9.0.

[0059] In some examples of this embodiment, the second calcination temperature is 350-450° C. Specifically, the second calcination time is 2-3 hours.

[0060] The preferred steps of the present invention are:

[0061] (1) Dissolve sucrose in water and stir until a clear and transparent solution is formed;

[0062] (2) subjecting the clear and transparent solution obtained in step (1) to a hydrothermal reaction, and naturally cooling to room temperature to obtain a brown-red precipitate;

[0063] (3) centrifuging, washing, and drying the brown-red precipitate obtained in step (2) with deionized water and anhydrous ethanol, and grinding and collecting the carbonaceous nanospheres;

[0064] (4) dispersing the carbonaceous nanospheres obtained in step (3) in an aqueous solution of anhydrous citric acid, ammonium heptamolybdate tetrahydrate, and ferric chloride hexahydrate, and obtaining a black precipitate after aging under condensation reflux conditions;

[0065] (5) the black precipitate obtained in step (4) is centrifuged, washed, and dried with anhydrous ethanol, the sample is collected by grinding, and then calcined in an air atmosphere to obtain Fe2(MoO4)3 with a hollow three-shell structure;

[0066] (6) placing the Fe2(MoO4)3 with a hollow three-shell structure obtained in step (5) and sulfur powder in the downstream and upstream of the gas flow respectively, and performing gas phase sulfurization under an argon atmosphere to obtain a MoS2 / FeS precursor with a hollow three-shell structure;

[0067] (7) The hollow three-shell structure MoS2 / FeS precursor obtained in step (6) is dispersed in a Tris buffer solution, dopamine hydrochloride is then added thereto and stirred, and the mixture is centrifuged and washed with deionized water and dried to obtain a MoS2 / FeS@PDA composite.

[0068] (8) The MoS2 / FeS@PDA composite obtained in step (7) is calcined under an argon atmosphere to obtain MoS2 / FeS@NC, which is a heterostructure transition metal sulfide / nitrogen-doped carbon nanocomposite material with a hollow three-shell structure.

[0069] Specifically, in step (1), the stirring time is 30 to 50 minutes, preferably 45 minutes.

[0070] In step (2), the reaction conditions of the hydrothermal process are: reaction at 160-190° C. for 1-1.5 h, and more preferably, the hydrothermal conditions are preferably 170° C. for 1 h.

[0071] In step (3), the centrifugation condition is to use deionized water and anhydrous ethanol, and centrifuge and wash 3 to 6 times. The centrifugation condition is preferably to use deionized water for 3 times and anhydrous ethanol for 2 times.

[0072] In step (4), the condensation reflux condition is 40-70° C., the continuous insulation stirring time is 12-60 h, and the optimal stirring time is 48 h.

[0073] In step (5), the calcination conditions are calcination at 450-550° C. for 2-3 h, and the calcination temperature is preferably calcination at 500° C. for 2 h.

[0074] In step (6), the calcination conditions are calcination at 350-550° C. for 3-5 hours, and the calcination temperature is preferably calcination at 400° C. for 3 hours.

[0075] In step (7), the stirring time is 12 to 48 hours, and the optimal stirring time is preferably 48 hours. The mixture is centrifuged and washed 3 to 6 times, and the centrifugation condition is preferably 4 times using deionized water.

[0076] In step (8), the calcination temperature is 350-550°C, and the optimal temperature is more preferably 400°C.

[0077] A third embodiment of the present invention provides an application of the above-mentioned heterogeneous hollow multi-shell structured nanocomposite material in the preparation of a sodium ion battery.

[0078] A fourth embodiment of the present invention provides a sodium ion battery negative electrode, comprising an active material, a conductive agent, a binder and a current collector, wherein the active material is the above-mentioned heterogeneous hollow multi-shell structure nanocomposite material.

[0079] In some examples of this implementation mode, the mass ratio of the active material, the conductive agent and the binder is 65-80:15-30:10-15.

[0080] In some examples of this implementation manner, the conductive agent is acetylene black, Ketjen black or carbon nanotubes, etc. Ketjen black has higher conductivity, and using Ketjen black as the conductive agent can reduce the amount of the conductive agent used.

[0081] In some examples of this embodiment, the binder is polyvinylidene fluoride, sodium carboxymethyl cellulose or polyacrylic acid. When polyvinylidene fluoride is used as the binder, an organic solvent is required to disperse the materials. When sodium carboxymethyl cellulose or polyacrylic acid is used as the binder, water is required to disperse the materials. The present invention preferably uses sodium carboxymethyl cellulose as the binder.

[0082] A fifth embodiment of the present invention provides a sodium ion battery, comprising a positive electrode, a negative electrode and a secondary electrolyte, wherein the negative electrode is the negative electrode of the sodium ion battery described above.

[0083] In some examples of this embodiment, the positive electrode is a sodium sheet.

[0084] In some examples of this implementation mode, the secondary electrolyte used is NP-005 and NC-034. The NP-005 electrolyte is sodium hexafluorophosphate, and the solvent is diethylene glycol dimethyl ether; the NC-034 electrolyte is sodium perchlorate, and the solvent is a mixed solution of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate (volume ratio is 1:1:1).

[0085] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0086] Example 1

[0087] A method for preparing a Fe2(MoO4)3 precursor with a hollow multi-shell structure comprises the following steps:

[0088] Under magnetic stirring, 4g sucrose was dissolved in 20ml water, and the sucrose solution was transferred to a reactor with a polytetrafluoroethylene liner (capacity 100mL) and heated at 170℃ for 1h. After cooling naturally to room temperature, the precipitate was collected by centrifugation, washed several times with deionized water and anhydrous ethanol in turn, and then dried in a blast drying oven at 60℃ for 6h to obtain brown-red carbon nanospheres. 2.85g anhydrous citric acid, 13.3g ferric chloride hexahydrate and 4.414g tetrahydrate ammonium heptamolybdate (molar ratio Fe:Mo=1:0.5) were dissolved in 10mL of anhydrous ethanol and 30ml of deionized water. 10mg of carbon nanospheres were dispersed in the mixed solution and ultrasonically treated for 60min. Then the above dispersion was heated to 40℃ under condensation reflux conditions and aged for 48h. After naturally cooling to room temperature, the precipitate was collected by centrifugation, washed several times with anhydrous ethanol, and then dried in a forced air drying oven at 60 °C for 6 h. The aged carbonaceous nanospheres were placed in a tubular furnace and calcined at 500 °C in an air atmosphere for 2 h to obtain a hollow multi-shell structured Fe2(MoO4)3 precursor.

[0089] The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the Fe2(MoO4)3 precursor sphere with hollow multi-shell structure obtained in this example are shown in Figure 2. Figure 1 (a) and Figure 1 (b) Figure 1 This shows that the Fe2(MoO4)3 precursor spheres prepared in this example are hollow three-shell structures.

[0090] Example 2

[0091] The Fe2(MoO4)3 precursor powder and sulfur powder prepared in Example 1 were placed in the downstream and upstream of the gas flow of the tube furnace, respectively, and calcined at 400°C for 3h in Ar gas to obtain black MoS2 / FeS. 80mg of MoS2 / FeS powder was dispersed in 100mL of Tris buffer solution (pH=8.5) and ultrasonicated for 1h to make it evenly dispersed. Subsequently, 30mg of dopamine hydrochloride was added to the above dispersion and stirred continuously for 8h. The precipitate was collected by centrifugation, washed several times with deionized water, and then dried in a 60°C forced air drying oven for 10h. The collected MoS2 / FeS@PDA was placed in a tube furnace and calcined at 400°C for 2h in an argon atmosphere to obtain MoS2 / FeS@NC with a hollow three-shell structure.

[0092] The scanning electron microscope images (SEM) and transmission electron microscope images (TEM) of the hollow three-shell heterostructure transition metal sulfide / nitrogen-doped carbon nanocomposite prepared in this embodiment are shown in Figures 1 and 2, respectively. Figure 2 (a) and Figure 2 (b) Figure 2(a) shows that the prepared MoS2 / FeS@NC has a nanosphere structure with a diameter of 800-2000 nm. Figure 2 (b) shows that the prepared MoS2 / FeS@NC has a hollow three-shell structure. From the X-ray powder diffraction pattern ( Figure 3 ) can prove the successful preparation of MoS2 / FeS@NC heterostructure.

[0093] Example 3

[0094] The Fe2(MoO4)3 precursor powder and sulfur powder prepared in Example 1 were placed in the downstream and upstream of the gas flow of the tube furnace, respectively, and calcined at 400°C for 3h in Ar gas to obtain black MoS2 / FeS. 80mg of MoS2 / FeS powder was dispersed in 100mL of Tris buffer solution (pH=8.5) and ultrasonicated for 1h to make it evenly dispersed. Subsequently, 30mg of dopamine hydrochloride was added to the above dispersion and stirred continuously for 8h. The precipitate was collected by centrifugation, washed several times with deionized water, and then dried in a 60°C forced air drying oven for 10h. The collected MoS2 / FeS@PDA was placed in a tube furnace and calcined at 350°C for 2h in an argon atmosphere to obtain MoS2 / FeS@NC with a hollow three-shell structure.

[0095] The hollow three-shell MoS2 / FeS@NC obtained in this example is used as the negative electrode material of the sodium ion battery. The negative electrode material, Ketjen black and sodium carboxymethyl cellulose are added to deionized water at a mass ratio of 8:1:1 and mixed evenly, then coated on copper foil and vacuum dried to obtain the negative electrode. The positive electrode used is a sodium sheet, the secondary electrolyte is NP-005, the electrolyte is sodium hexafluorophosphate, and the solvent is diethylene glycol dimethyl ether. The sodium ion battery is assembled. The XPS total spectrum ( Figure 4 ) can confirm the existence of five elements: Mo, Fe, S, N and C.

[0096] Example 4

[0097] The Fe2(MoO4)3 precursor powder and sulfur powder prepared in Example 1 were placed in the downstream and upstream of the gas flow of the tube furnace, respectively, and calcined at 400°C for 3h in Ar gas to obtain black MoS2 / FeS. 80mg of MoS2 / FeS powder was dispersed in 100mL of Tris buffer solution (pH=8.5) and ultrasonicated for 1h to make it evenly dispersed. Subsequently, 30mg of dopamine hydrochloride was added to the above dispersion and stirred continuously for 8h. The precipitate was collected by centrifugation, washed several times with deionized water, and then dried in a 60°C forced air drying oven for 10h. The collected MoS2 / FeS@PDA was placed in a tube furnace and calcined at 350°C for 2h in an argon atmosphere to obtain MoS2 / FeS@NC with a hollow three-shell structure.

[0098] The hollow three-shell MoS2 / FeS@NC obtained in this embodiment is used as the negative electrode material of the sodium ion battery. The negative electrode material, Ketjen black and sodium carboxymethyl cellulose are added to deionized water at a mass ratio of 7:2:1 and mixed evenly, then coated on copper foil and vacuum dried to obtain the negative electrode. The positive electrode used is a sodium sheet, the secondary electrolyte used is NP-005, wherein the electrolyte is sodium hexafluorophosphate, and the solvent is diethylene glycol dimethyl ether. The sodium ion battery is assembled. –1 The discharge capacity is 349.3 mA h g after 3000 cycles of charge and discharge at a current density of –1 See Figure 5 .

[0099] Example 5

[0100] The Fe2(MoO4)3 precursor powder and sulfur powder prepared in Example 1 were placed in the downstream and upstream of the gas flow of the tube furnace, respectively, and calcined at 400°C for 3h in Ar gas to obtain black MoS2 / FeS. 80mg of MoS2 / FeS powder was dispersed in 100mL of Tris buffer solution (pH=8.5) and ultrasonicated for 1h to make it evenly dispersed. Subsequently, 30mg of dopamine hydrochloride was added to the above dispersion and stirred continuously for 8h. The precipitate was collected by centrifugation, washed several times with deionized water, and then dried in a 60°C forced air drying oven for 10h. The collected MoS2 / FeS@PDA was placed in a tube furnace and calcined at 350°C for 2h in an argon atmosphere to obtain MoS2 / FeS@NC with a hollow three-shell structure.

[0101] The hollow three-shell MoS2 / FeS@NC obtained in this embodiment is used as the negative electrode material of the sodium ion battery. The negative electrode material, Ketjen black and sodium carboxymethyl cellulose are added to deionized water at a mass ratio of 7:2:1 and mixed evenly. Then, the mixture is coated on a copper foil and vacuum dried to obtain the negative electrode. The positive electrode used is a sodium sheet, and the secondary electrolyte used is NP-005, in which the electrolyte is sodium hexafluorophosphate and the solvent is diethylene glycol dimethyl ether. The sodium ion battery is assembled. The current density is tested at 0.1 to 10A. –1 At a current density of Figure 6 . At 0.1, 0.2, 0.5, 1, 2, 5 and 10Ag –1 At current densities of 688.5, 558.73, 486.02, 460.48, 427.17, 400.21 and 372.67 mA h g -1 The discharge capacity.

[0102] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A nanocomposite material with a heterogeneous hollow multi-shell structure, characterized in that: The nanocomposite material is formed by nitrogen-doped carbon coated on the surface of a bimetallic sulfide, and the bimetallic sulfide is formed by a composite of MoS2 and FeS; the nanocomposite material is a porous hollow multi-shell nanosphere structure, and gaps are left between the shells inside the hollow multi-shell structure.

2. The heterogeneous hollow multi-shell structure nanocomposite material according to claim 1, characterized in that: The diameter of the nanosphere structure is 800 to 2000 nm.

3. A method for preparing the heterogeneous hollow multi-shell structure nanocomposite material according to claim 1, characterized in that: The steps include: Sucrose is dissolved in water and subjected to hydrothermal reaction to obtain carbonaceous nanospheres; The carbon nanospheres are aged in a mixed solution of trivalent iron salt, trivalent molybdenum salt and citric acid, and the aged carbon nanospheres are first calcined in an air atmosphere to obtain a hollow three-shell Fe2(MoO4)3 precursor; The Fe2(MoO4)3 precursor and sulfur powder are subjected to a vapor phase sulfurization treatment in an inert atmosphere to obtain a hollow three-shell MoS2 / FeS; MoS2 / FeS is mixed with dopamine, and dopamine polymerization is performed to obtain a polydopamine-coated MoS2 / FeS precursor; Under inert atmosphere conditions, the polydopamine-coated MoS2 / FeS precursor is subjected to a second calcination to obtain the product.

4. The method for preparing the heterogeneous hollow multi-shell structure nanocomposite material according to claim 3, characterized in that: The molar ratio of ferric salt to molybdate is 1:0.45-0.55; Or, the temperature of the hydrothermal reaction is 160-190°C and the time is 1-1.5h; Alternatively, the aging temperature is 40-70°C.

5. The method for preparing the heterogeneous hollow multi-shell structure nanocomposite material according to claim 3, characterized in that: In the aging solution, the solvent used is a mixture of water and ethanol, preferably, the volume ratio of ethanol to water is 1:2.5-3.5; Or, the temperature of the first calcination is 450-550°C; Or, the pH of the dopamine polymerization reaction is 8.0 to 9.0; Alternatively, the temperature of the second calcination is 350-450°C.

6. Use of a nanocomposite material with a heterogeneous hollow multi-shell structure as claimed in claim 1 or 2 or a nanocomposite material with a heterogeneous hollow multi-shell structure obtained by the preparation method according to any one of claims 3 to 5 in the preparation of a sodium ion battery.

7. A sodium ion battery negative electrode, comprising an active material, a conductive agent, a binder and a current collector, characterized in that: The active substance is the heterogeneous hollow multi-shell structure nanocomposite material according to claim 1 or 2 or the heterogeneous hollow multi-shell structure nanocomposite material obtained by the preparation method according to any one of claims 3 to 5.

8. The sodium ion battery negative electrode according to claim 7, characterized in that: The mass ratio of active material, conductive agent and binder is 65-80:15-30:10-15; Or, the conductive agent is acetylene black, Ketjen black or carbon nanotubes; Alternatively, the binder is polyvinylidene fluoride, sodium carboxymethyl cellulose or polyacrylic acid.

9. A sodium ion battery comprising a positive electrode, a negative electrode and a secondary electrolyte, characterized in that: The negative electrode is the negative electrode of the sodium ion battery mentioned above.

10. The sodium ion battery according to claim 9, characterized in that: The positive electrode is a sodium sheet.

Citation Information

Patent Citations

  • Nanoparticle-encapsulated multi-core multi-shell hollow material as well as preparation method and application thereof

    CN113363434A

  • Carbon sphere-coated multi-sphere nickel-molybdenum bimetallic selenide composite material and preparation method thereof

    CN117542983A

  • Metal sulfur selenide / carbon composite hollow nanosphere as well as preparation method and application thereof

    CN118588896A

  • Mxene-iron-molybdenum bimetallic sulfide and carbon composite material as well as preparation method and application thereof

    CN119240798A